Electronic transport in anisotropic disordered quantum wire - Kaya, Tuncer (WORLD SCIENTIFIC PUBL CO PTE LTD, 2008)
We have investigated the transport properties of anisotropic disordered quantum wire by the method of energy level statistics and transfer matrix method. We have found a general average conductance relation in terms of the anisotropy parameter t, disorder strength W, and the cross-sectional area, A, of the wire. From the available numerical data, we have also shown that the anisotropic correlation length t can be related to the isotropic correlation length xi as xi(t) similar or equal to t(2)xi, for L similar or equal to A and xi(t) similar or equal to t xi, for L >> A. Here, L is the length of the wire. In addition, anisotropic dependence of conductance fluctuation and conductance distribution have been studied to a certain extent.
Keywords: quantum transport; quantum wires; conductance distribution; random matrix theory; METAL-INSULATOR-TRANSITION; CRITICAL-BEHAVIOR; ANDERSON LOCALIZATION; LEVEL STATISTICS; SCALING THEORY; SI-P; CONDUCTIVITY; TEMPERATURE; DIFFUSION; SPACINGS; Physics